EMPLOYEE SALARY PAYMENT SYSTEM ON PT. CARGOPOLAKARYA JAYALESTARI - Diana Lestari; Susi Wagiyati. Skom. MMSi (Jurnal Sistem Informasi, 2000)
With the existence of a good computerized system within a company will get anaccurate calculation of salaries, the administration does not need to enter repetitivedata payroll data, saving time, effort and money.Corporate leaders can easily and quickly find information and error informationreceived by the head company is unlikely because the data are computer processedaccurately done, employees can find out in a clear and easy on the calculation of hissalary in a month, facilitate the re-search data.